The Concept Of Science In Philosophy Review (Study Aspects Of Ontology, Epistemology And Axiology Of Science) - Hayati, Nursri; Dalimunthe, Irwan Saleh (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2023)
This paper discusses the concept of Science in the context of a philosophical review. A philosophical review is an examination of the concept of science through ontology, epistemology, and axiology. According to the findings of this study, ontology of science investigates the nature of a science's existence or the nature of a science's existent object of study. Science studies both matter and immaterial objects. The classification of science is often separated into two, namely religious science and general science, based on the aim of study of science. Epistemology is the method, source, and condition of a science's validity. Allah SWT is the source of knowledge in Islam. Additionally, man observes and experiments on the verses of Allah SWT using the senses, mind and intuition. Axiology is the science of value. The Axiology of science is in the framework of the implementation of human duties, namely abd`Allah and khalifah fil ardh.